The efficacy of split tibial tendon transfers on functional gait outcomes for children and youth with cerebral palsy and spastic equinovarus foot deformities. (1st May 2023) - Hochstetter-Owen, Jennifer; Stott, Susan; Williams, Sîan A.
Abstract : Aims: To systematically review the efficacy of split tendon transfer surgery on gait-related outcomes for children and adolescents with cerebral palsy (CP) and spastic equinovarus foot deformity. Methods: Five databases (CENTRAL, CINAHL, PubMed, Embase, Web of Science) were systematically screened for studies investigating split tibialis anterior or split tibialis posterior tendon transfer for spastic equinovarus foot deformity, with gait-related outcomes (published pre-September 2022). Study quality and evidence were assessed using the Methodological Index for Non-Randomized Studies, the Risk of Bias In Non-Randomized Studies of Interventions, and the Grading of Recommendations Assessment, Development and Evaluation. Results: Overall, 17 studies (566 feet) were included: 13 studies used clinical grading criteria to report a postoperative 'success' of 87% (75% to 100%), 14 reported on orthotic use with 88% reduced postoperative use, and one study reported on ankle kinematics improvements. Ten studies reported post-surgical complications at a rate of 11/390 feet (2.8%), but 84 feet (14.8%) had recurrent varus (68 feet, 12%) or occurrence of valgus (16 feet, 2.8%). Only one study included a patient-reported outcome measure (pain). Conclusion: Split tendon transfers are an effective treatment for children and youth with CP and spastic equinovarus foot deformities. Clinical data presented can be used for future study designs; a more standardized functional and patient-focused approach to evaluating outcomes of surgical intervention of gait may be warranted. Cite this article: Bone Jt Open 2023;4(5):283–298.